Inhabit the City: rights, policies and challenges. A case study of Bairro Padre Cruz in Lisbon - Di Giovanni, C. (2019)
According to Lefebvre, the right to the city constitutes a request for the construction of urban life able to respond to the needs of everyone. However, this presents difficult to achieve as for evictions, occupations, illegal settlements and the “weakness” of public social housing in some contexts such as countries of Southern Europe. In Lisbon, is chosen Bairro Padre Cruz as a case study due to the interventions in progress within, in order to face the socio-spatial segregation that characterizes many public neighborhoods. Included in the Urban Rehabilitation Strategy of Lisbon Municipality, the intervention has a lengthy work schedule, aiming to the housing improvement with a new urban project and the involvement of local actors in a horizontal process. The methodology of regeneration of alvenarias (masonry) seems to correspond to the application of the principle of deliberative democracy defined in the right to the city. However, the first incursions in the neighborhood and the conversations with residents, researchers and technicians are revealing a scenario also filled with conflicts and disagreements. The present communication is a beginning and ongoing research within the PhD thesis project in Urban Studies of ISCTE-IUL / FCSH-UNL, focused on analyze and evaluate integrated interventions in social housing through a comparison with the Italian approach and a fieldwork in Lisbon.